Impact of Target Games Training Method and Coordination Ability on Futsal Shooting Performance: Evidence from Extracurricular Players at Dinamika Pembangunan I Jakarta - Rizki Ronaldo; Defliyanto Defliyanto; Moch. Asmawi; Johansyah Lubis; Oman Unju Subandi; Yarmani Yarmani; Jerome Angelitud Porto (Sriwijaya University Learning and Education International Journal, 2024)
This study aimed to compare the effectiveness of the Girshoot Target Game and Zig-Zag Goal Target training methods in improving futsal shooting skills while considering students’ coordination levels (high and low). The study was conducted at SMK Dinamika Pembangunan I Jakarta using a 2 × 2 factorial experimental design. The population consisted of 107 students who participated in extracurricular futsal activities. Data were analyzed using two-way ANOVA to examine the effects of training methods, coordination levels, and their interaction on shooting performance. The results indicated significant differences in shooting skills between students trained using the Girshoot Target Game method and those trained using the Zig-Zag Goal Target method. Significant differences were also found between students with high and low coordination levels. Furthermore, a significant interaction effect was observed between training methods and coordination levels on shooting performance. The Girshoot Target Game method was found to be more effective for students with high coordination, whereas the Zig-Zag Goal Target method was more beneficial for students with low coordination. These findings suggest that the effectiveness of shooting training methods depends on players’ coordination abilities. Therefore, futsal coaches should consider coordination levels when designing training programs to maximize shooting performance and skill development.